2018
DOI: 10.1002/lno.10789
|View full text |Cite
|
Sign up to set email alerts
|

Additive response to multiple environmental stressors in the seagrass Zostera marina L.

Abstract: Ongoing climate changes alter a broad range environmental variables in coastal ecosystems, which may lead to changes in species range distributions or collapse of populations. It is often assumed that changes in environmental parameters affect organisms in a nonadditive way and multifactorial experiments are therefore needed to obtain a better prediction of the effects of climate change. We studied experimentally how combinations of high temperature, low light and high nitrogen (HN) availability affect eelgras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 78 publications
5
32
0
Order By: Relevance
“…Our results are in line with previous studies which did not observe interactive effects of both factors on adult temperate seagrass plants (Touchette and Burkholder, 2002;Kaldy, 2014;Moreno-Marín et al, 2018;Mvungi and Pillay, 2019;Ontoria et al, 2019) and tropical seagrass plants (Viana et al, in prep). In these studies, the combination of effects of nutrient enrichment of the water column and increasing temperature did not show clear effects on seagrass plants.…”
Section: Seedling Response To Increased Nutrientssupporting
confidence: 94%
See 2 more Smart Citations
“…Our results are in line with previous studies which did not observe interactive effects of both factors on adult temperate seagrass plants (Touchette and Burkholder, 2002;Kaldy, 2014;Moreno-Marín et al, 2018;Mvungi and Pillay, 2019;Ontoria et al, 2019) and tropical seagrass plants (Viana et al, in prep). In these studies, the combination of effects of nutrient enrichment of the water column and increasing temperature did not show clear effects on seagrass plants.…”
Section: Seedling Response To Increased Nutrientssupporting
confidence: 94%
“…In contrast, other previous studies showed that morphological traits, such as leaf length, growth or number of leaves per shoot, were the most variable traits under the influence of both factors (Bintz et al, 2003;Mvungi and Pillay, 2019). Interactive effects on the response in the %N of the leaves were only observed in Z. marina (Moreno-Marín et al, 2018). Otherwise, interactive effects were observed when temperature was combined with other nutrient sources such as labile organic C in the sediment in C. nodosa (Ontoria et al, 2019).…”
Section: Seedling Response To Increased Nutrientsmentioning
confidence: 56%
See 1 more Smart Citation
“…Therefore, the interaction between stressors is now viewed as a critical issue, and it is suggested that single-factor experiments are not adequate for assessing the effects of several disturbances on coastal marine ecosystems (Wernberg et al, 2012;Todgham and Stillman, 2013;Ontoria et al, 2019b). In the last years, an increasing number of papers aiming to understand cumulative impacts of stressors have exponentially increased (Gunderson et al, 2016;Adams et al, 2020;Stockbridge et al, 2020), and more empirical data on the effects of the interaction of increasing temperature and nutrient over-enrichment at an individual level has been obtained (Touchette and Burkholder, 2002;Bintz et al, 2003;Touchette et al, 2003;Burnell et al, 2013;Kaldy, 2014;Kaldy et al, 2017;Egea et al, 2018;Moreno-Marín et al, 2018;Mvungi and Pillay, 2019;Ontoria et al, 2019b). Nevertheless, responses depend on their local adaptation and life history traits (Tuya et al, 2019;Anton et al, 2020) are species-specific, and to our knowledge, there is very limited information about the combined effects of these two stressors in any tropical seagrasses species (Artika et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Additional physiological stress is put on plants during the summer because of increasing water temperature and decreasing light levels caused by epiphytic and drift algae (Park andLee 2007, CCE 2011). Since eelgrass stops growing at water temperatures above 20°C and can lose shoot weight at 25-30°C (Touchette et al 2003;Moreno-Marín et al 2018), plant growth was not an accurate measurement of transplant success for this experiment. Therefore, conducting this study during fall or spring may have facilitated better establishment and growth.…”
Section: Discussionmentioning
confidence: 99%